The effect of inflation on the optimum payback cut-off - J. U. De Villiers (South African Journal of Business Management, 1991)
Despite the theoretical criticisms against it, payback is one of the most commonly used methods of investment appraisal in practice. Its ease of calculation and simplicity are seen as its most important advantages. In addition, an unsophisticated method like payback can yield the correct investment decision as long as the correct cut-off is specified. In this paper the optimum payback cut-off and how it is influenced by inflation is studied. Three different methods of calculating payback under inflation are investigated. In all of these the optimum cut-off depends upon the type of assets (current, depreciable or non-depreciable assets) as well as the life of depreciable assets employed. The study shows that the optimum nominal payback cut-off (where the payback calculation is based on inflated cash flows) decreases with increasing inflation for all asset types. The optimum real payback cut-off (based on nominal cash flows adjusted for inflation) does not change with inflation. The optimum uninflated payback cut-off (where inflation is ignored) decreases rapidly with inflation for projects employing current assets. In the paper is shown that complex but systematic relationships exist between a project's payback period and its discount rate. Despite its deficiencies, the use of the payback method is therefore not entirely irrational.
Keywords: 650